Experimental study on nonlinear hygroscopic and strength behavior of mudstone under coupled temperature and humidity conditions for underground engineering - Weisheng Zhao; Lijun Han; Shuai Yan; Wei He (Scientific Reports)
Abstract The hygroscopic behavior of mudstone and its water content significantly influence the stability of underground engineering structures. This study investigated the hygroscopic behavior of mudstone under coupled temperature and humidity conditions and its effect on mechanical properties through hygroscopicity experiments and uniaxial compression tests. A hygroscopic mathematical model was developed, and the physical significance of the model’s coefficients was clarified. Additionally, coefficient of variation (CV) analysis was conducted to examine water content deviations during the hygroscopic process. The results indicated that the equilibrium water content (EWC) exhibited a three-stage growth pattern with increasing humidity: rapid growth (0‒20% RH), slow growth (20‒60% RH), and accelerated growth (60‒100% RH), whereas it decreased with increasing temperature, although the rate of decrease slowed progressively. The EWC of small samples (φ15 mm), which can reach 12.22%, was much greater than that of standard mechanical samples (φ50 mm), whose EWC was less than 4%. A low-humidity environment (≤ 80%RH) or a relatively high temperature (e.g., 30℃) effectively reduced water content deviations. An increasing water content resulted in a linear decline in the uniaxial compressive strength (UCS) and elastic modulus (E), with humidity accelerating mechanical degradation, whereas at high humidity levels, increasing the temperature had a moderate positive effect on the mechanical properties. Humidity was the dominant factor influencing the hygroscopic behavior of mudstone, and reducing the environmental humidity significantly decreased the EWC, improving the mechanical properties of mudstone. On the basis of these findings, a high-temperature and low-humidity environmental optimization strategy was proposed to mitigate the adverse effects of hygroscopic behavior on mechanical properties and to enhance the long-term stability of engineering structures. This study revealed the nonlinear hygroscopic-mechanical behavior of mudstone under coupled temperature and humidity conditions, providing a scientific basis for environmental temperature and humidity regulation and structural stability optimization in underground engineering.